The Cytoplasmic Region of Inner Helix S6 Is an Important Determinant of Cardiac Ryanodine Receptor Channel Gating - Sun, Bo (J Biol Chem, 2016)
The ryanodine receptor (RyR) channel pore is formed by four S6 inner helices, with its intracellular gate located at the S6 helix bundle crossing region. The cytoplasmic region of the extended S6 helix is held by the U motif of the central domain and is thought to control the opening and closing of the S6 helix bundle. However, the functional significance of the S6 cytoplasmic region in channel gating is unknown. Here we assessed the role of the S6 cytoplasmic region in the function of cardiac RyR (RyR2) via structure-guided site-directed mutagenesis. We mutated each residue in the S6 cytoplasmic region of the mouse RyR2 ((4876)QQEQVKEDM(4884)) and characterized their functional impact. We found that mutations Q4876A, V4880A, K4881A, and M4884A, located mainly on one side of the S6 helix that faces the U motif, enhanced basal channel activity and the sensitivity to Ca(2+) or caffeine activation, whereas mutations Q4877A, E4878A, Q4879A, and D4883A, located largely on the opposite side of S6, suppressed channel activity. Furthermore, V4880A, a cardiac arrhythmia-associated mutation, markedly enhanced the frequency of spontaneous openings and the sensitivity to cytosolic and luminal Ca(2+) activation of single RyR2 channels. V4880A also increased the propensity and reduced the threshold for arrhythmogenic spontaneous Ca(2+) release in HEK293 cells. Collectively, our data suggest that interactions between the cytoplasmic region of S6 and the U motif of RyR2 are important for stabilizing the closed state of the channel. Mutations in the S6/U motif domain interface likely destabilize the closed state of RyR2, resulting in enhanced basal channel activity and sensitivity to activation and increased propensity for spontaneous Ca(2+) release and cardiac arrhythmias.